Nucleophile-initiated thiol-michael reactions: Effect of organocatalyst, thiol, and Ene - Chan, J.; Hoyle, C.; Lowe, Andrew; Bowman, M. (American Chemical Society, 2010)
A detailed evaluation of the kinetics of the thiol-Michael reaction between hexanethiol and hexyl acrylate is described. It is shown that primary amines are more effective catalysts than either secondary or tertiary amines with, for example, quantitative conversion being achieved within 500 s in the case of hexylamine with an apparent rate constant of 53.4 mol L-1 s -1 at a catalyst loading of 0.057 mol %. Certain tertiary phosphines, and especially tri-n-propylphosphine and dimethylphenylphosphine, are shown to be even more effective species even at concentrations 2 orders of magnitude lower than employed for hexylamine and performed in solution with quantitative conversions reached within ca. 100 s for both species and apparent rate constants of 1810 and 431 mol L-1 s-1, respectively. The nature of the thiol is also demonstrated to be an important consideration with mercaptoglycolate and mercaptopropionate esters being significantly more reactive than hexanethiol with reactivity mirroring the pKa of the thiols. Likewise, it is shown that the structure of the activated ene is also crucial with the degree of activation and ene-substitution pattern being important features in determining reactivity. In terms of reaction with hexanethiol in the presence of hexylamine as catalyst, it is shown that propylmaleimide > diethyl fumarate > diethyl maleate > dimethylacrylamide > acrylonitrile > ethyl crotonate > ethyl cinnamate > ethyl methacrylate. © 2010 American Chemical Society.